Peran LAZISMU (Lembaga Amil Zakat, Infaq dan Sadaqah Muhammadiyah) dalam Mengentaskan Kemiskinan Masyarakat Kota Medan - Ahmad Suwandi; Yenni Samri (Management of Zakat and Waqf Journal (MAZAWA), 2022)
Poverty describes a condition of low ownership and income, or in more detail describes a condition that basic human needs cannot be fulfilled, namely food, shelter, and clothing. The purpose of this study is to find out how the amil zakat infaq and alms Muhammadiyah institutions help alleviate poverty in the community. Data collected through interviews with LAZISMU administrators were analyzed using qualitative techniques in this study. In addition to conducting interviews, documentation is used to perform data mining procedures. The source triangulation technique is used in the data validation methodology. The process of collecting, reducing, presenting, and verifying data are used in data analysis. Based on the results of the study, the first ZIS fund collection mechanism carried out by LAZISMU Medan city is through recommendations from people closest to prospective mustahik, the second is collaborating with branch leaders through recording Mustahik data. After the process of recording and collecting data on mustahik candidates, the program division will conduct a survey by paying attention to certain conditions or conditions for mustahik candidates. Through interviews with several informants, it can be concluded that the beneficiaries of the ZIS fund assistance experienced social changes and were helped economically, although only in the form of basic necessities but it helped the economy a little for the poor with the assistance they received